(The preparation of monoglyceride from coconut oil as emulsifier) - Djubaedah, Endah; Moestafa, Achmad; -, Mariana (Balai Besar Industri Agro, 1995)
Food emulsifier is an important addive used in food industries.Emulsifiers are usedto improve the texture of products such as to stabilize margarine,ice cream,etc.Basically emulsifier consist of two functional groups, the first one dissolves in water and the other in oil which enebles them to bridge two unmixed phases.The most widely used emulsifiers are monoglyceride which contain long alkyl chain residue from fatty acid chain and hydroxyl groups from glycerol.Monoglycerida had been prepared in this study through the reaction of coconut oil and glycerol using coustic soda as catalyst.The best treatment was obtained from the reaction of one parts of coconut oil and four parts of glycerol at 250 degree C, stirred for 3 hours using of 0.20% NaOH as catalyst which produced 45% yield containing 77% monoglyceride.